(untitled) (LACCEI, 2024)
The objective of this research was to identify the forms of use of social media, lifestyle habits and to identify if there are links with academic performance, for this purpose a structured self-administered questionnaire was applied to a sample of 588 undergraduate students from two public universities in Peru. To identify the relationships between the variables, bivariate correlation analysis, and hierarchical correlation analysis were performed. The results indicate that students are characterized by having a lifestyle of few hours of sleep, very little time devoted to physical activity, and considerable time devoted to social media for entertainment and non-academic purposes. On the other hand, there is a direct relationship between time spent on social media and the scale measuring excessive use of social media, which reveals that there are indications of excessive use of social media that can negatively affect academic performance.